The Disappearing Technology and Products of Traditional Tibetan Village Blacksmiths - Chandra L. Reedy (Heritage, 2024)
Tibetans have a long history of iron mining, smelting, and forging. For centuries, craftsmen in major cities and large iron production centers made high-quality swords and suits of armor, as well as decorative iron ritual objects for monasteries and the elites, but blacksmithing workshops in small villages have always produced and repaired everyday objects for agricultural and home use. Modern political changes, along with greater availability of industrial objects in local markets, have greatly reduced the rank of the village blacksmith. Ethnographic fieldwork reported here from two Tibetan Bön villages in the Aba Tibetan and Qiang Autonomous Prefecture, China (once part of traditional Amdo area of Tibet), highlights some of the threats to the continued existence of village blacksmiths. Both a part-time blacksmith in one village and a full-time blacksmith in another make only a marginal living from their work. Their descendants are unlikely to continue the business. Many of the village blacksmiths in the area have already stopped production and closed their workshops. It is likely that the village blacksmith tradition might soon disappear altogether in this region of the world without support. Preservation of this tradition could benefit both cultural and environmental sustainability goals.